2018
DOI: 10.21037/jtd.2017.12.27
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the key transcription factors in esophageal squamous cell carcinoma

Abstract: Background: Esophageal cancer (EC) is a common human malignancy worldwide. Esophageal squamous cell carcinoma (ESCC) is the predominant subtype in China. The tumorigenesis mechanism in ESCC is unclear. The aim of this study was to identify key transcription factors (TFs) in ESCC and elucidate the mechanism of it. Methods: A total of ten published microarray datasets of ESCC was downloaded from the Gene Expression

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…Recent studies have indicated that SOX10 regulates EMT in cancer [33,34]. This finding was further supported in our GSEA of GEO databases using HALLMARK gene collection (Fig.…”
Section: Resultssupporting
confidence: 86%
“…Recent studies have indicated that SOX10 regulates EMT in cancer [33,34]. This finding was further supported in our GSEA of GEO databases using HALLMARK gene collection (Fig.…”
Section: Resultssupporting
confidence: 86%
“…Recently, studies have found that the expression of certain genes, such as MCT4, ZNF750, Gli1, etc. was highly related to the occurrence and development of ESCC, and they might be applied as ideal biomarkers for ESCC (Cheng et al, 2018; Nambara et al, 2017; Yang et al, 2017; Zhang et al, 2018b). In addition, the aberrant expression of a few collagen family genes has also been reported to be significantly associated with the prognosis of ESCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…BUB1B is also expressed at a high level in lung adenocarcinoma, and the overexpression of BUB1B is associated with poor disease progression and poor survival rates in patients with lung adenocarcinoma (37). Certain transcription factors can regulate ESCC cancer cell cycle by regulating BUB1B, which is a cell cycle-related DEG, thereby promoting the development of ESCC (38). Therefore, BUB1B may promote the development of ESCC by deregulating the cell cycle.…”
Section: Discussionmentioning
confidence: 99%